2019
DOI: 10.1002/adfm.201807282
|View full text |Cite
|
Sign up to set email alerts
|

Toward Chirality‐Encoded Domain Wall Logic

Abstract: Nonvolatile logic networks based on spintronic and nanomagnetic technologies have the potential to create high‐speed, ultralow power computational architectures. This article explores the feasibility of “chirality‐encoded domain wall logic,” a nanomagnetic logic architecture where data are encoded by the chiral structures of mobile domain walls in networks of ferromagnetic nanowires and processed by the chiral structures' interactions with geometric features of the networks. High‐resolution magnetic imaging is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Thus, we conclude the small degree of DFD stochasticity observed in a minority of the Tb-doped devices was likely due to variability in the magnetisation structure of injected DWs, as opposed to inherently stochastic interaction of the DWs with the defect sites. This is an important distinction, as many studies have demonstrated the feasibility of controlling the initial structure/chirality of DWs 6,24,50,51 , while the dynamic interactions of DWs with defect sites is inherently uncontrollable at fields above H WB…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we conclude the small degree of DFD stochasticity observed in a minority of the Tb-doped devices was likely due to variability in the magnetisation structure of injected DWs, as opposed to inherently stochastic interaction of the DWs with the defect sites. This is an important distinction, as many studies have demonstrated the feasibility of controlling the initial structure/chirality of DWs 6,24,50,51 , while the dynamic interactions of DWs with defect sites is inherently uncontrollable at fields above H WB…”
Section: Resultsmentioning
confidence: 99%
“…19,20 In the absence of any external magnetic field or pinning of the domain wall, the domain wall velocity increases with the current density up to saturation 21 , either expanding or contracting the domain depending on the direction of the applied current. Magnetic domain wall devices have been utilized previously for binary logic 22,23,24,25,26,27 and memory 28,29 applications.…”
mentioning
confidence: 99%
“…In the past three years, however, there has been a flurry of studies showing reward-related neuronal activity in the cerebellum [6][7][8][9][10][11][12] . What are reward signals doing in an error-correcting part of the brain?…”
Section: See-hun Yangmentioning
confidence: 99%
“…The DMI both establishes a specific chirality and favours the generation of the correct type of wall -a Néel wall -in Luo and colleagues' set-up. Researchers have previously recognized that chiral domain walls could be used in logic operations 6 , but an all-electrical working logic has been hampered by the lack of a reliable working inverter, the key component for logic operations.…”
mentioning
confidence: 99%